Demography of cape petrels in response to environmental changes. Issue 1 (10th July 2022) - Sauser, Christophe; Delord, Karine; Barbraud, Christophe
Abstract: Predicting the responses of populations in changing environments is an important task for ecologists. Understanding the population dynamics of high‐latitude breeding species is critical given the particularly rapid environmental changes that occur in these regions. Using long‐term mark–resighting data acquired over 53‐years in Pointe Géologie, Terre Adélie, Antarctica, we estimated age‐specific demographic parameters and evaluated the effect of the environment on survival of a poorly known species, the cape petrel Daption capense . We then modeled the dynamics of this population using a life‐history model and performed prospective and retrospective analyses to estimate the sensitivity of the population growth rate to demographic parameters, and to quantify their relative contribution. Survival of cape petrel increased with age, being 0.610 (±0.193) for juveniles, 0.739 (±0.158) for individuals from 2 to 4, and 0.920 (±0.031) for older individuals. Minimum age at first reproduction was 3 years old, the age at which all birds were recruited was 14 years, and mean age at first reproduction was 9.05 (±2.06) years. Adult survival increased over time and was positively correlated with the southern annular mode (SAM). The stochastic population growth rate was estimated at 1.019, and adult survival over age 5 made the largest contribution to variance of the population growth rate. Sensitivity analyses revealed that population regulation was mainly driven by the SAM. Our results suggest that despite the decrease in breeding success, the population of cape petrels at Pointe Géologie increased due to the increase in immature and adult survival. Abstract : Using long‐term mark‐resighting data, we estimated age‐specific demographic parameters and assessed the sensitivity of the growth rate of the cape petrel population in Terre Adélie, Antarctica. The results showed that environmental variation had contrasting effects on different vital rates, but indicated that increasing survival, linked to a positive trend in SAM, mainly contributed to the growth of the population over the past decades, despite a negative trend in breeding success mainly due to increased predation pressure and perhaps sea ice changes.